Implementasi Penguatan Destinasi Pariwisata Daerah Melalui Analisis Strata dan Pesaing Produk Unggulan Kota Pekalongan - Andjar Prasetyo (JURNAL LITBANG KOTA PEKALONGAN, 2021)
The purpose of the research is to determine and analyze the strata and competitor products, as well as compile options policy recommendations of tourism for the City of Pekalongan. Located in Pekalongan City, from June - November 2021, mix methods with descriptive explorative as a method of research. Secondary Data from the Government of Pekalongan City, the primary data obtained through questionnaires open the 132 respondents and the questionnaire analysis of 56 respondents with Likert scale. Analysis with Three Levels of a Product and the Five Forces. The result strata featured product is batik as a core product, Megono as actual product and Tauto, Coffee as the augmented product, a score between 5-7 points that the products featured on the condition of the potentially claimed as the featured product. The accumulation of the results of the Analysis of Five Forces, that the featured products in support of the tourism are still very in need of strengthening. This research implies that to encourage the increase of tourism in the City of Pekalongan needed to support the strengthening of the featured products on the internal side of the featured products and revamping the external side.  Keywords: Featured products, tourism, three levels of a product, five forces